Sebuah Tinjauan Literature Review: Intention To Leave - Hernita, Nita; Merry Marianti, Maria; Deti, Regina (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Theoretical research on intention to leave (ITL) is an attempt to understand the elements that influence individuals' willingness to leave the organization where they work. In this context, theories such as Theory of organizational behavior, Theory of planned behavior, Theory of work life balance (WLB), Theory of Sustainable Business Practice (TSPB), Self Determination Theory (SDT), Human Resource Management (HRM), social exchange theory (SET) are often used as frameworks to explain this phenomenon. In this study, an in-depth analysis was conducted of the various factors that can influence intention to leave (ITL), data collection methods and theories underlying ITL were clearly discussed using the PRISMA method by collecting data through google scholar, researchgate and publish or perish, 220 articles were excluded and included. Data synthesis of 49 articles. The results of this study can provide valuable insights for human resource managers and practitioners in developing strategies to minimize ITL in the workplace. In addition, this theoretical study can also serve as a foundation for future empirical research to examine the relationship between these factors in a more specific context.